Inflation Linkages Within The Eurozone: Core vs. Periphery. (16th June 2018) - Magkonis, Georgios; Sharma, Abhijit
Abstract: We examine the process of inflation transmission among GIIPS countries (Greece, Ireland, Italy, Portugal and Spain) and Germany. Our findings suggest that inflation spillovers have increased since 2001. We also find that peripheral economies are (dis‐)inflation transmitters to the core. This finding is significant for policy formulation, given the very low inflation environment that currently exists in the Euro area and the macroeconomic implications that arise from this.